Gendered Langauge Use By Teachers And Classroom Communication At Tertiary Level - Amna Saeed; Iram Saleem; Rabia Saeed (Elementary Education Online, 2023)
This paper studies the gender and gendered language use in classroom environment and their effects on communication between the teacher and the students at tertiary level. It also studies whether any gender bias or discrimination enters the classroom environment through either the teacher’s or the learners’ gender and use of language or their behavior. Apart from that, the other variables such as motivation, language proficiency, level of participation of learners in class, co-education environment, age of the teacher, attitude and behavior of the teacher, and other social and cultural factors etc. are also discussed which can affect the communication between teacher and the learners. For this purpose, a survey has been conducted. A closed ended questionnaire, comprises 18 questions, was designed to analyze the main variables gender and gendered language use along with other aforementioned factors for the selected students studying at tertiary level in a local language university in Islamabad, Pakistan. The questionnaire was distributed among forty students, twenty males and twenty females, to conduct the survey. The findings obtained from quantitative analysis of the responses revealed the students’ concept of gender and gendered language use and the issues related to them in classroom environment and their effects on communication between teacher and students. The students’ responses were discussed in detail from the theoretical perspective of Deborah Tannen’s Genderlect Thoery (1990) and Kabira and Masinjila’s Gender Analysis Framework (1997). The findings also revealed that students were in favour of the necessity of healthy and gender neutral educational environment for the maximum learning and smooth communication between the teacher and the students.